2014
DOI: 10.1299/mej.2014smm0032
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion analysis of silane coupling agent/copper interface with density functional theory

Abstract: Nanotechnology devices with strong adhesion strength are required due to the miniaturization and reduction of the thickness of electronic devices. This paper describes a technique to select a silane coupling agent effective for obtaining the strong adhesion with copper by use of a density functional theory (DFT) in addition to an experimental peel test. We calculated the adhesion energy at the interface between three candidate silane coupling agents, aminoethyl-aminopropyltrimethoxysilane (AEAPS), mercaptoprop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…For instance, PI surfaces treated with amine solutions exhibited optimal adhesion at specific drying temperatures, linked to the molecular weight of the amines [34]. Additionally, a study combining peel tests and density functional theory (DFT) simulations revealed aminoethylaminopropyltrimethoxysilane (AEAPS) as an effective silane agent for Cu adhesion, supported by high adhesion energy and peel strength findings [35]. These insights align with our observations in Fig.…”
Section: Addition To Improve Adhesion Strength Of Pspisupporting
confidence: 83%
See 1 more Smart Citation
“…For instance, PI surfaces treated with amine solutions exhibited optimal adhesion at specific drying temperatures, linked to the molecular weight of the amines [34]. Additionally, a study combining peel tests and density functional theory (DFT) simulations revealed aminoethylaminopropyltrimethoxysilane (AEAPS) as an effective silane agent for Cu adhesion, supported by high adhesion energy and peel strength findings [35]. These insights align with our observations in Fig.…”
Section: Addition To Improve Adhesion Strength Of Pspisupporting
confidence: 83%
“…This change can be attributed to the plasma's ability to introduce polar functional groups, increasing the number of binding sites and thus improving wettability. Enhanced wettability is vital, allowing the polyimide to achieve more extensive contact with the substrate [27][28][29].…”
Section: Surface Pretreatmentmentioning
confidence: 99%
“…Among all theoretical methods, quantum chemistry calculations have been proven to be a very powerful tool to evaluate the reactivity of molecules and its tendency to protect the metal from corrosion through the determination of molecular structure as well as electronic structure [14][15][16][17][18][19][20][21]. With this method, the anti-corrosion performance of the coating molecule can be predicted by calculations of global reactivity parameters, such as energy gap (∆E) between HOMO and LUMO, global hardness ( ), electronegativity (χ), dipole moment (µ), number of electrons transferred (∆N), etc., and such prediction of corrosion protection performance leads to a rational method to identify molecules for perfect anticorrosion coating [2,22] The existing literature in these regards majorly focuses on the molecular structure and the adhesion analysis [23] of coating ingredients on the corrosion protection of metal substrates.…”
Section: Introductionmentioning
confidence: 99%